2013
DOI: 10.1002/pola.26848
|View full text |Cite
|
Sign up to set email alerts
|

Efficient stabilization of thiol-ene formulations in radical photopolymerization

Abstract: Various phenolic radical inhibitors were tested to improve storage stability of thiol‐ene formulations. After determining the optimal inhibitor, a synergetic effect was discovered when it was used in combination with acidic buffer, thus preventing premature dark gelation while maintaining desired photoreactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 27 publications
0
91
0
1
Order By: Relevance
“…The limited shelf‐life stability of thiol–enes may be also caused by a base‐catalyzed nucleophilic addition of thiol to the ene double bond . Recently, Liska and coworkers described an efficient stabilizer system for thiol–ene formulations based on the combination of a free radical scavenger and an acid with an appropriate p K a value. Thus, the combination of a moderately strong acid coadditive such as the phenyl phosphonic acid (pK a = ∼2) with a small amount of pyrogallol (0.1% wt) was also tested for AMC.…”
Section: Resultsmentioning
confidence: 99%
“…The limited shelf‐life stability of thiol–enes may be also caused by a base‐catalyzed nucleophilic addition of thiol to the ene double bond . Recently, Liska and coworkers described an efficient stabilizer system for thiol–ene formulations based on the combination of a free radical scavenger and an acid with an appropriate p K a value. Thus, the combination of a moderately strong acid coadditive such as the phenyl phosphonic acid (pK a = ∼2) with a small amount of pyrogallol (0.1% wt) was also tested for AMC.…”
Section: Resultsmentioning
confidence: 99%
“…All three formulations were then homogenized in an ultrasonic bath for ≈30 min. In addition, the thiol‐based formulation (2M/EDDT) was stabilized by 9 × 10 −3 m PG and 90 × 10 −3 m MA …”
Section: Methodsmentioning
confidence: 99%
“…Although vinyl esters are generally not as reactive as their acrylate analogs, our recent work demonstrated that the thiol-ene photo-click chemistry could greatly improve the reactivity of vinyl esters even to the level of acrylates [37]. Moreover, it is important to mention that the poor storage stability related to thiol-ene systems have recently been solved by using a combination of radical and acidic stabilizing system [38]. All these aspects suggest that water-soluble vinyl esters are promising hydrogel precursors for photolithography-based AMTs and tissue engineering applications.…”
Section: Chemistry Of Hydrogel Formationmentioning
confidence: 95%